2009
DOI: 10.12741/ebrasilis.v2i1.35
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la alternación de fuentes sanguíneas sobre la fecundidad y la fertilidad de Rhodnius prolixus Stal (Heteroptera: Reduviidae).

Abstract: Resumen. En este trabajo se evidencia que si el éxito reproductivo de Rhodnius prolixus Stål está relacionado a la fuente alimentaria, entonces las necesidades biológicas del insecto son satisfechas en modos diferentes según el tipo de alternancia entre dichas fuentes de alimentación; tales diferencias son reveladas mediante los cambios en fertilidad y fecundidad del insecto. Se realizaron nueve alternancias, en cada una se suministraron dos alimentaciones, en unas se alternó la fuente de alimentación y en los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
5
1
1
Order By: Relevance
“…These results were in disagreement with those proposed by several authors, who mention differences in nutritional quality and reproductive parameters between bugs feeding on mammalian versus avian hosts (Diotaiuti & Dias, 1987;Gomes et al, 1990;Guarneri et al, 2000;Nattero et al, 2011). In turn, the ingestion of combined blood sources did not result in significant differences in the number of chorionated oocytes present in females, in contrast to what was proposed by Aldana et al (2009). In this context, our findings are in line with the ones described by Jiron & Zeledón (1982) for T. infestans, who suggest a similar weight gain between the bugs being offered one or multiple sources of blood under experimental conditions, regardless of the host-feeding source.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…These results were in disagreement with those proposed by several authors, who mention differences in nutritional quality and reproductive parameters between bugs feeding on mammalian versus avian hosts (Diotaiuti & Dias, 1987;Gomes et al, 1990;Guarneri et al, 2000;Nattero et al, 2011). In turn, the ingestion of combined blood sources did not result in significant differences in the number of chorionated oocytes present in females, in contrast to what was proposed by Aldana et al (2009). In this context, our findings are in line with the ones described by Jiron & Zeledón (1982) for T. infestans, who suggest a similar weight gain between the bugs being offered one or multiple sources of blood under experimental conditions, regardless of the host-feeding source.…”
Section: Discussioncontrasting
confidence: 96%
“…For the analysis, T. infestans that fed on more than one host were grouped in two categories: (a) the mammalian-bird category, comprising insects that fed on chicken and on at least one mammalian host (dog, goat and/or human); (b) the mammalianmammalian category, comprising insects that fed on different mammalian hosts. This criterion was based on the extensive bibliography that demonstrated that the quality of blood from the selected hosts influenced the biological requirements of triatomines (Diotaiuti & Dias, 1987;Gomes et al, 1990;Aldana et al, 2009;Nattero et al, 2011).…”
Section: Feeding Sourcementioning
confidence: 99%
“…blood meals in the field would reduce survival and/or lower the number of eggs an adult female triatomine can lay. [29][30][31][32] Other hypotheses (e.g., higher mortality, leaving the houses, and not laying eggs because of maladaptation to the domiciliary conditions) could also explain the almost null fecundity, extremely low immature survival, and low adult survival required to fit our field data.…”
Section: Discussionmentioning
confidence: 95%
“…Las gallinas son fuentes de alimento para los triatominos y su presencia en las aéreas domiciliarias impactan la ecología doméstica de la enfermedad de Chagas, ya que, incrementan la infestación del domicilio, conllevando a un incremento en el contacto del vector con los reservorios domésticos, aumentando de esta manera el número de triatominos infectados 35,36 . En este sentido ha sido sugerido que el éxito reproductivo de R. prolixus se ve favorecido con mayor fecundidad si en el domicilio ocurriera la ingesta con sangre humana, pero si previamente el insecto se ha alimentado sobre gallina 37 .…”
Section: Discussionunclassified